Decline in numbers of Antarctic skuas breeding at Potter Peninsula, King George Island, Antarctica - Graña Grilli, Maricel
The Brown Skua (Stercorarius antarcticus lonnbergi) and the South Polar Skua (S. maccormicki) breed in Antarctica and, in the case of Brown Skua, on sub-Antarctic islands (Ritz et al. 2008). During the austral summer breeding season, they feed both on land and at sea. Their broad diet includes penguins and other seabirds (mainly eggs and chicks), fish, krill and carrion (Reinhardt et al. 2000). Where nesting is sympatric, the Brown Skua monopolizes terrestrial food sources (especially penguin colonies), forcing the South Polar Skua to rely mostly on marine resources (Pietz 1987, Hahn et al. 2008, Malzof & Quintana 2008, Montalti et al. 2009, Graña Grilli & Montalti 2012). Fil: Graña Grilli, Maricel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina